Investigation on low-cycle fatigue performance of high-strength steel bars including the effect of inelastic buckling. (1st December 2022) - Wu, Dianqi; Ding, Yang; Su, Junsheng; Li, Zhong-Xian; Zong, Liang
Highlights: Experimentally compare monotonic and low-cycle fatigue performance of HTRB600 and HRB400E steel bars. Study the effects of yield strength, slenderness ratio, strain amplitude and rebar diameter on low-cycle fatigue properties of reinforcing bars. Propose a low-cycle fatigue life prediction model considering the effect of inelastic buckling. Calibrate buckling and low-cycle fatigue parameters for reinforcing steel bars by a valid FEM method. Abstract: Bar buckling and subsequently low-cycle fatigue fracture is one of the main failure modes of RC columns/piers under strong earthquakes. Due to the adoption of new metallurgical technology and possibly enduring higher stress, high-strength steel bars (HSSB) may be more prone to occur buckling and low-cycle fatigue failure, which will detrimentally affect the seismic performance of RC columns/piers. In view of this, this paper studies the buckling and low-cycle fatigue performance of high-strength steel bars (HSSB) HTRB600 and compares with normal steel bars (NSB) HRB400E. At first, the monotonic tensile and compressive tests of HTRB600 and HRB400E steel bars with different slenderness ratios ( L/D = 6, 8, 10, 12, 15) were conducted to study their monotonic tensile and compressive properties. Then, the low-cycle fatigue tests of HTRB600 and HRB400E reinforcing steel with different strain amplitudes and slenderness ratios were conducted to evaluate their low-cycle fatigue performance. The fatigue life prediction formulas for HTRB600 and HRB400E steel bars taking into account the effects of inelastic buckling were proposed through the regression analysis of test results. Moreover, the fractured surfaces obtained by the scanning electron microscope (SEM) were used to compare the low-cycle fatigue failure features of HTRB600 and HRB400E steel bars. Finally, a finite element model (FEM) was developed to simulate the nonlinear mechanical behaviors of HTRB600 and HRB400E steel bars under monotonic and cyclic loading. Test results show that HTRB600 steel bars present lower tensile ductility, more severe post-buckling softening and pinching effect than HRB400E steel bars. The increase in yield strength, buckling length and strain amplitude will reduce the low-cycle fatigue life of steel bars. The range of striation marks observed from low-cycle fatigue fractured surfaces by SEM for HTRB600 steel bar is smaller than HRB400E steel. The calibrated buckling and low-cycle fatigue parameters by the validated finite element model (FEM) can be adopted to accurately simulate the inelastic seismic response of RC structures.